2022
DOI: 10.1097/fpc.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cytochrome P450 2C19 polymorphisms on the clinical efficacy and safety of voriconazole: an update systematic review and meta-analysis

Abstract: Objective To assess the impact of cytochrome P450 (CYP) 2C19 polymorphisms on the clinical efficacy and safety of voriconazole. Methods We systematically searched PubMed, EMBASE, CENTRAL, ClinicalTrials.gov, and three Chinese databases from their inception to 18 March 2021 using a predefined search algorithm to identify relevant studies. Studies that reported voriconazole-treated patients and information on CYP2C19 polymorphisms were included. The efficacy outcome was success rate. The safety outcomes includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…17 Our previous systematic review showed that CYP2C19 polymorphisms significantly affected VRC steady-state valley concentration (C min ss) and corresponding efficacy and safety in clinical practice. 19,20 CYP2C19 polymorphisms were also proved to guide initial dose selections, which led to a better clinical outcome in the treatment of IA. 21 Therefore, whether CYP2C19 polymorphisms could still guide individualized medication under inflammatory state is a focus of the present study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Our previous systematic review showed that CYP2C19 polymorphisms significantly affected VRC steady-state valley concentration (C min ss) and corresponding efficacy and safety in clinical practice. 19,20 CYP2C19 polymorphisms were also proved to guide initial dose selections, which led to a better clinical outcome in the treatment of IA. 21 Therefore, whether CYP2C19 polymorphisms could still guide individualized medication under inflammatory state is a focus of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…CYP2C19 is the primary enzyme responsible for the conversion of VRC into its major inactive metabolite, VRC N‐oxide (VNO), which accounts for approximately 72% of plasma metabolites 17 . Our previous systematic review showed that CYP2C19 polymorphisms significantly affected VRC steady‐state valley concentration (C min ss) and corresponding efficacy and safety in clinical practice 19,20 . CYP2C19 polymorphisms were also proved to guide initial dose selections, which led to a better clinical outcome in the treatment of IA 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Of these, CYP2C19 polymorphisms are considered a key determinant of the wide pharmacokinetic (PK) variability of VRC 16 . Low levels of exposure to VRC may result in treatment failure, whereas high levels of exposure may result in adverse neurological effects, hepatotoxicity, and visual impairment 17–19 . Therefore, the dosing schedule for VRC should be optimized to maximize the best therapeutic effect and minimize the occurrence of adverse effects.…”
mentioning
confidence: 99%